2020
DOI: 10.1039/d0nj01274b
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and biological evaluation of novel nicotinamide derivatives as potential histone deacetylase-3 inhibitors

Abstract: The selected nicotinamide-based HDACi displayed selectivity towards HDAC3 over pan HDAC and exhibited potent cytotoxicity against the used cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…This inhibitory potential against hERG could be minimized to 1.33 µM by applying derivatization strategies from similar studies [93]. Hamoud et al [94] [97]. In contrast to the assumed chelation by the thiazolidinedione moiety as in previous studies [98], docking results suggested chelation via the amide carbonyl.…”
Section: Non-classic Benzamidesmentioning
confidence: 95%
See 1 more Smart Citation
“…This inhibitory potential against hERG could be minimized to 1.33 µM by applying derivatization strategies from similar studies [93]. Hamoud et al [94] [97]. In contrast to the assumed chelation by the thiazolidinedione moiety as in previous studies [98], docking results suggested chelation via the amide carbonyl.…”
Section: Non-classic Benzamidesmentioning
confidence: 95%
“…This inhibitory potential against hERG could be minimized to 1.33 µM by applying derivatization strategies from similar studies [ 93 ]. Hamoud et al [ 94 ] used the nicotinamide moiety as an alternative ZBG and varied the cap group. They could show that compound 25 was the most potent in the series, showing an inhibitory activity of 4.64 µM against Hela nuclear extract and 690 nM toward HDAC3.…”
Section: Non-classic Benzamidesmentioning
confidence: 99%
“…In continuation of our ongoing efforts to design and study HDAC3 specific inhibitors, ,,, in this present study we report N -(2-aminophenyl)-5-(benzylamino)­pyrazine-2-carboxamide (PT3), a novel benzamide class, HDAC3 i as a brain penetrant memory enhancer. PT3 has been designed and developed by our group as a novel HDAC3 selective inhibitor and has previously been reported as a lead molecule for its anticancer properties when compared to the standards (Figure ) BG45 and CI994 .…”
Section: Introductionmentioning
confidence: 88%
“…Hamoud and co-workers recently designed and synthesized some N -(4-(2-arylidenehydrazine-1-carbonyl) phenyl) nicotinamide derivatives as potent and HDAC3-selective inhibitors. Pyridine being a bioisostere of benzene, the benzamide ZBG group was replaced with the m -pyridyl carboxamide ZBG function.…”
Section: Hdac3-selective Inhibitorsmentioning
confidence: 99%